Religious service - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows a man in white robe with arms raised standing in a church behind a low stone wall. He may be standing in a baptismal pool. Behind him is a backdrop which depicts the river Jordan. A microphone stands in front of him. At the left of the photograph stands a man in a suit. Visible at the very bottom of the photograph are hats worn by some of the seated congregation.